GEOCHEMICAL FACIES OF THE TURONIAN GONGILA FORMATION, BORNU (CHAD) BASIN, NIGERIA: IMPLICATION FOR PROVENANCE, PALEOCLIMATE AND PALEOWEATHERING CONDITIONS - Shettima, B.; Adams, F. D.; Haruna, A. I.; Goro, A. I.; Bukar, M. (International Journal of Research -GRANTHAALAYAH, 2018)
Geochemical evaluation of the Gongila Formation of Bornu (Chad) Basin indicated mineralogical compositions of quartz, feldspar, anatase, gypsum, smectite and kaolinite from XRD analysis. Corresponding major oxides from XRF analysis indicated the dominance of SiO2 with an average of 54.91 wt % followed by Al2O3 with 15.92 wt %. CaO, NaO, K2O, MgO, MnO, Fe2O3 TiO2 and P2O5 occurred with average compositions of 1.87%, 1.02%, 2.15%, 1.17%, 0.06%, 3.04%, 0.03% and 1.52 % respectively. Alteration indexes derivations from these oxides consisting of Chemical Index of Alteration (CIA), Plagioclase Index of Alteration (PIA) and Chemical Index of Weathering (CIW) accounted for a dominantly moderate weathering condition for the formation. Discriminant plots of Fe2O3+MgO versus TiO2 indicated a tectonically passive source area composed of generally intermediate igneous rocks, affirmed by Al2O3 versus TiO2 bivariate model with skewed plot along the granite line. The dominance of smectite suggests prevalence of arid to semi-arid paleoclimatic conditions during the deposition of shales of the Gongila Formation. Intermittent phases of superposed tropical climate are also depicted by the subordinate kaolinite mineralization.